KAJIAN PENGARUH SEDIMENTASI PADA KINERJA PENGOPERASIAN WADUK KEDUNG OMBO - Anggita Inges Wari; Bimby Octavia Kurniasari; Sumbogo Pranoto; Suharyanto Suharyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Kedung Ombo is a multi-purposes reservoir used for flood control, hydropower generation, irrigation services, raw water supply, fisheries and tourism. To meet the water demand (demand), the performance of the reservoir should run well. Over time, sedimentation in reservoir increases. Sedimentation problems may affect the operating performance of the reservoir. If sedimentation increases, the effective volume will be reduced then as a result water demand (demand) can not be fulfilled. Therefore, a further study on operating performance Kedung Ombo Reservoir in relation to sedimentation is needed . The results showed that the simulation the best method SOP for some conditions of sedimentation, in year-on-0, the 15th year, and year-to-27 is not seen a significant difference from the value of the operating performance. So it can be concluded that sedimentation is not very big significant on the operation of the reservoir.